Bangladesh's pathways to climate-resilient development: A methodical review - Md. Arfanuzzaman (World Development Sustainability, 2024)
Climate resilient development pathways (CRDP) are procedures that reinforce sustainable development and reduce poverty and inequalities while meeting adaptation and mitigation targets. The study systematically assessed Bangladesh's efforts to combat climate change and evaluated its progress toward CRDP with a degree of confidence approach. It also assessed climate change vulnerability, national climate change plans and policies, climate finance conditions, and environmental sustainability. The study revealed that the recent climate change plans and strategies have transformative, social inclusiveness, gender responsiveness, climate resilience, institutional flexibility and coordination, and target setting and monitoring attributes from a moderate to large extent. However, to implement its recently developed climate plans like the Mujib Climate Prosperity Plan, Delta Plan, NAP, and NDC, where funding is essential—the nation needs USD 533.7 billion. The study suggests that though the country has implemented several plans and strategies in recent decades, uneven progress has appeared in some important socio-economic and environmental indicators as well as SDGs which signifies low return against investment. It can be concluded that ensuring maximum socio-economic and environmental return on investment, long-term climate finance, strengthening local govt. organizations, adopting region specific and holistic approaches with private sector engagement would advance CRDP attainment as well as a nature positive economy and system transition in Bangladesh.